The Arterial Branching Pattern of the Common Femoral Artery: A Case Report - Devika Agnihotri; Parul Upadhayay; Shaifaly M Rustagi; Tushita Nanda (Journal of Medical Academics)
Many interventional procedures are performed on the femoral arteries in the region of the femoral triangle. They give branches that form collateral circulation through various anastomoses. In the present study, a case of variation in femoral arteries has been reported. The deep femoral artery (DFA) originated as one of the bifurcations of the common femoral artery (CFA) just below the inguinal ligament on both sides. The origin, position, and branches of the femoral arteries were studied along with a relevant review of the literature and its applied aspect has been discussed.